TATA RUANG KANTOR DAN PENGARUHNYA TERHADAP SEMANGAT KERJA PEGAWAI PADA PERUSAHAAN AIR MINUM PT TIRTAARTHA BUANAMULIA DI KEDONGANAN BADUNG - I Gusti Gde Oka Pradnyana; Putu Sri Agustini (Forum Manajemen, 2013)
The arrangement of office lay out in the company need a good attentionin order that the good lay out will give some benefit among others : the work willrunning well , a better traffic of work , and will be easier in controlling .The aim of this research is to know if there an influence of the office lay out to theemployees mentality in the Mineral Water Company Pt. Tirta Artha Buana Mulia.Some hypothesis that applied are there is a sinificant influence of office lay out tothe employee’s mentality mentality in The Mineral Water Company Pt. Tirta ArthaBuana Mulia. The population in this research is an employees of The MineralWater Company Pt. Tirta Artha Buana Mulia with 84 samples . The method of datacollecting is using correlational decriptif , and regression analysis technique whichis counted using version 16.0 SPSS analysis . The result of this research is shownthat the hypothesis of office lay out is accepted and significanttly influenced to the employees menthality in The Mineral Water Company Pt. Tirta Artha Buana Mulia,which is proofed by the figures of t-count = 14.125 is bigger than the table value= 1.989 using believable degree of 95% and failure degree of 5%. Meanwhile theinfluence of the office lay out to the employee’s mentality in the The Mineral WaterCompany Pt. Tirta Artha Buana Mulia is 70.9% and the rest is 29.1% influencedby unresearched factors. Based on this research , it is suggested to the head of TheMineral Water Company Pt. Tirta Artha Buana Mulia to keep giving attention to theoffice lay out such as the desk , chair , light , and cleanness , in others to support thework of the office so the employees menthality will be raised .